2023
DOI: 10.1161/circimaging.122.015089
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Dysfunction in Significant Atrial Functional Mitral Regurgitation: Phenotypes and Prognostic Implications

Abstract: BACKGROUND: Atrial functional mitral regurgitation (AFMR) is associated with increased morbidity and mortality. Left atrial (LA) size and function in AFMR are poorly characterized. We aimed to assess LA function by reservoir strain (LASr) and estimated reservoir work (LAWr) and their impact on outcome in AFMR. METHODS: Consecutive patients at our institution between 2001 and 2019 and with significant (moderate or greater) AFMR were examined. LAWr was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…LA function assessment with estimation of LARS and LA reservoir work (LARW) was more significant compared to size measurement only. [ 15 ] Inciardi et al showed that impaired LA function parameters appear earlier in SMR compared to LA size increase. [ 16 ] In addition, LARS may also be more indicative of LA fibrosis than LA size.…”
Section: The Role Of the Left Atrium In Atrial Secondary Mitral Regur...mentioning
confidence: 99%
“…LA function assessment with estimation of LARS and LA reservoir work (LARW) was more significant compared to size measurement only. [ 15 ] Inciardi et al showed that impaired LA function parameters appear earlier in SMR compared to LA size increase. [ 16 ] In addition, LARS may also be more indicative of LA fibrosis than LA size.…”
Section: The Role Of the Left Atrium In Atrial Secondary Mitral Regur...mentioning
confidence: 99%
“…The latter is influenced by LA size, contractility, and compliance. In their work, Cramariouc et al 6 provide further insight into the LA size and function in those with moderate or greater severity of AFMR. They have described LA mechanics in 3 clinical phenotypes of AFMR: those with AF only, those with HFpEF only, and those with HFpE and AF.…”
Section: See Article By Cramariuc Et Almentioning
confidence: 99%
“…5 However, these prevalence rates from epidemiological data do not distinguish between those with and without a history of AF. In this issue of the Circulation Cardiovascular Imaging , Cramariuc et al 6 report that 63% of patients with all HFpEF patients and 24% those without history of AF had moderate or greater degree of AFMR. Since echocardiography is the basis to categorize functional MR into ventricular FMR or AFMR, the data from the national echocardiographic database from Australia (NEDA) are also instructive.…”
mentioning
confidence: 99%
“…Percutaneous mitral valve repair through transcatheter edge-to-edge repair (TEER) is widely demonstrated to be able to reduce the grade of MR in patients at high surgical risk [ 3 , 4 ]. In the MR untreated scenario, the development of LA cardiomyopathy has been demonstrated to occur, as it progressively determines cellular and structural alterations that predispose to the development of atrial fibrillation (AF) [ 5 , 6 , 7 ]. Similarly, LV assumes a more spherical shape, with broad LV wall stress and end-diastolic pressure, hence leading to a decreased contractile state, with reduced myofiber content and interstitial fibrosis [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Standard deviation,2 Heart failure with preserved ejection fraction;3 Heart failure with mildly reduced ejection fraction;4 Heart failure with reduced ejection fraction; 5 Chronic obstructive pulmonary disease;6 Chronic kidney disease;7 Atrial fibrillation; 8 Society of Thoracic Surgeons;9 Mitral regurgitation; 10 Cardiac implantable electronic devices;11 Implantable cardioverter-defibrillators;12 Cardiac resynchronization therapy device with defibrillator.…”
mentioning
confidence: 99%